Studies in Modern Jewish and Hindu Thought - Chatterjee, M. author. aut Link
IX, 181 p.
Keywords: The book compares modern Jewish and Hindu thought through discussing selected writers with reference to common issues treated by them, issues which are still relevant today. The writers are Mahatma Gandhi, Max Nordau, A.D. Gordon, Martin Buber, Sri Aurobindo, Rav Kook and Rabindranath Tagore. The issues include the following: the critique of civilisation, the concept of labour, self-definition vis-a-vis 'east' and 'west', the pursuit of 'realisation' either individually or collectively, the use of evolution as a resource concept, and the critique of nationalism which ran parallel to its pursuit.